2014
DOI: 10.5941/myco.2014.42.1.59
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Thermotolerance of Entomopathogenic Isaria fumosorosea SFP-198 Conidial Powder by Controlling the Moisture Content Using Drying and Adjuvants

Abstract: Entomopathogenic fungi are promising pest-control agents but their industrial applicability is limited by their thermosusceptibility. With an aim to increase the thermotolerance of Isaria fumosorosea SFP-198, moisture absorbents were added to dried conidial powder, and the relationship between its water potential and thermotolerance was investigated. Mycotized rice grains were dried at 10℃, 20℃, 30℃, and 40℃ and the drying effect of each temperature for 24, 48, 96, and 140 hr was determined. Drying for 48 hr a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…Conidia stored with these materials and exposed to 50 ºC for two hours showed no significant decrease in viability, while the germination was reduced by 10, 17 and 23% for unformulated conidia and conidia stored with silica gel and or with zeolite, respectively. It is surprising that those materials with higher hydric retention capacity, i.e., silica gel and zeolite, did not enhance the thermotolerance, because other studies have shown that this property may protect spores when exposed to high temperatures (McClatchie et al, 1994;Moore et al, 1996;Kim et al, 2014a). It is possible that the higher proportion of material used in this study has influenced conidial viability.…”
Section: Discussionmentioning
confidence: 45%
See 2 more Smart Citations
“…Conidia stored with these materials and exposed to 50 ºC for two hours showed no significant decrease in viability, while the germination was reduced by 10, 17 and 23% for unformulated conidia and conidia stored with silica gel and or with zeolite, respectively. It is surprising that those materials with higher hydric retention capacity, i.e., silica gel and zeolite, did not enhance the thermotolerance, because other studies have shown that this property may protect spores when exposed to high temperatures (McClatchie et al, 1994;Moore et al, 1996;Kim et al, 2014a). It is possible that the higher proportion of material used in this study has influenced conidial viability.…”
Section: Discussionmentioning
confidence: 45%
“…Some authors have observed that the addition of silica gel to oil formulations of M. anisopliae favors conidial viability due to the capacity of this material to adsorb humidity (McClatchie et al, 1994;Moore et al, 1996). Other studies have shown that the use of different desiccant materials enhances the conidial thermotolerance of the entomopathogenic fungi Isaria fumorosea and correlate this with water potential (Kim et al, 2014a). Thus, it is important for the ingredients in the formulation to have properties that favor the high temperature resistance of infective units and that can maintain suitable humidity conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bell & Hamal (1974) reported that B. bassiana, Metarrhizium anisopliae and Metarhizium rileyi fungi spores maintained their virulence to insects after three years stored at -20 o C in tubes containing silica gel crystals (a synthetic product made by the silicate reaction of sodium and sulfuric acid) compared to those without silica gel. Kim et al (2014) have also confirmed higher thermotolerance mediated by Si compounds, through moisture retention, for the insect-parasitic fungus Cordyceps fumosorosea. The higher resistance to fungus applied under field conditions may have potentiated the degree of synergism between Bb+KSil observed in the present work in terms of CE%.…”
Section: Treatmentmentioning
confidence: 54%
“…This synergism has been demonstrated through different interactions, including the breakdown of lipid barriers in the insect cuticle by the K 2 SiO 3 , facilitating the fungi penetration and colonization of the insect body (Storm et al, 2016). The synergism between the fungus B. bassiana and K 2 SiO 3 increased the mortality of the two-spotted spider mite, Tetranychus urticae (Acari: Tetranychidae), in mono and dicotyledonous plants (Gatarayiha et al, 2010), and thermotolerance and pathogenicity of fungus spores (Kim et al, 2014).…”
Section: Introductionmentioning
confidence: 99%